(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Kokan Khanate, which emerged during the formation of new Uzbek states covering the 16th-19th centuries, along with the high development of science and cultural life, did not lag behind the development of poetry and art. When talking about the literary atmosphere of the Kokan Khanate, we should mention Umar Khan and Nadirabegim separately. Because their creativity and the comfort they created for the people of creativity not only contributed to the literature of the Kokhan Khanate, but also to the development of Uzbek literature. In this article, the great development of classical literature along with the creative path of Umarkhan and Nodirabegim will be widely covered based on the sources.